PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS SD - yulianti, fitria; indrawati, tin; nasrul, nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
1 This study aims to determine whether the effect of probem - based learning model is significant on the student’ learning outcomes  of  sosial subject. The type of research is quantitative research. This research employed an experimental research of True experimental design. The research design in the Pretest-Posttest ControlDesign Group.Based on the pretest conducted in the experimental class, the average score of the student is 64.75 while score of the control 64,90. After the posttest was given to both classes, the average score obtained by the experimental class is 80,0 whilethe average scoreof the control 74.55. the hypthesis testing obtainet a tcountof 3.54 and ttableof 2.02 with α = 0.05, which means that tcount ttable. Therefore,it is concluded that Problem - Based Learning mode has a significant effect on the student’ Learning outcomes of  sosial science subject in Grade V of  Elementary school Number 13 Parit Putus, Ampek angkek Sub-district, Agam district.  Keyword :PBL Model,Learning outcome IPS